Intensity of pain and biochemical changes in blood plasma in spinal cord trauma - Yamamotová, A; Srámková, T; Rokyta, R (Spinal cord, 2010)
STUDY DESIGN: Cross-sectional, observational and longitudinal. OBJECTIVES: The aim of the study was to analyze the relationship between pain intensity, plasma lipids and severity of spinal cord injuries in patients with paraplegia (n = 11), tetraplegia (n = 16) and polytrauma (n = 15). We concentrated on the hospitalization period immediately following injury. METHODS: Pain intensity was assessed on a visual analog scale immediately after patients were transported to hospital, again 14 days after injury and before discharge from hospital. Blood samples were also obtained at these same times. We measured following biochemical parameters: total protein, albumin, total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, glycemia, and C-reactive protein. Data were analyzed with respect to type of injury, state of unconsciousness immediately after injury, hemorrhage, measure of liability (self-inflicted injuries vs casualties), cause of the accident and pre-injury cholesterol levels. RESULTS: On the day of injury, pain intensity correlated positively with HDL cholesterol (r = 0.48, P = 0.04); on the day of discharge from hospital, pain intensity correlated positively with blood glucose levels (r = 0.67, P = 0.0002). Diagnostic subgroups did not differ either in pain intensity or in pain dynamics during hospitalization. Total cholesterol level was lowest in patients with polytrauma. In all patients, the lowest total cholesterol level was observed immediately after injury. HDL cholesterol was highest after injury. CONCLUSION: After spinal cord injury, lower total cholesterol levels reflected more serious trauma intensity and HDL cholesterol predicted more intensive pain. Subjects responsible for their own injuries suffered less intensive pain than those who were not responsible for their injuries.
Keywords: Spinal Cord Neoplasms; dospělí; Female; Pain Measurement; C-Reactive Protein; Adult; mladý dospělý; ženské pohlaví; průřezové studie; longitudinální studie; lipidy; lidé; pozorování; Lipids; měření bolesti; sérový albumin; Blood Proteins; bolest; krevní proteiny; Cross-Sectional Studies; Male; Aged; Observation; Young Adult; Pain; Serum Albumin; lidé středního věku; C-reaktivní protein; senioři; mužské pohlaví; nádory míchy; Middle Aged; Paralysis; Longitudinal Studies; paralýza; Humans